Continuous meteorological observations at station BERMS Old Jack Pine, 2014-2015 - Warren Helgason (PANGAEA, 2017)
This dataset contains meteorological observations such as pressure, temperature and precipitation measurements during the years 2014 and 2015 at station BERMS Old Jack Pine (Saskachewan, Canada).